Erratum to "Forty years of computers & chemical engineering: A bibliometric analysis" [Computers & Chemical Engineering 141 (2020) 106978]. (September 2021) - Modak, Nikunja Mohan; Lee, Jay H.; Merigó, José M.
Highlights: Professor Rajagopalan Srinivasan at IIT Madras, India should have been the one with the statistics displayed in the table 5A, rank #16 instead of Professor Ramesh Srinivasan from University of California Irvine, USA. The University and the Country of ``Srinivasan, R'' are respectively corrected as IIT Madras and India in Table 5b, rank 33.